A Preliminary Survey on Geospatial Distribution of Aedes albopictus and Aedes aegypti Mosquitoes Found in Different Urban and Rural Locations of Southern West Bengal, India: Distribution of Aedes mosquitoes in Southern West Bengal, India - Majumdar , Anasuya; Mahata , Amit; Bag, Shampa (Journal of Tropical Life Science, 2024)
Aedes mosquitoes are globally known to transmit various arboviral diseases including Dengue fever. Historically considered an urban disease, Dengue fever has been reported in rural areas of different countries also. Two important species, Aedes aegypti, and Aedes albopictus, are rapidly spreading and invading new locations in India and risking human health more frequently each year. Since vector control has been proven to be the most effective measure to prevent such disease, knowing the vectors more, would help design successful methods to fight against the disease. In this survey, a cross-sectional inspection was conducted to look for the existence of Aedes spp. at 420 locations including urban and rural areas of 15 districts in Southern West Bengal, India, Morphological identification of collected specimens, comparative analyses of vector distribution and their breeding habitats, between districts, rural and urban locations as well as between different physiographic regions in this area were performed. The study revealed that sixty-four percent of the urban locations inspected and 22% of the rural locations inspected were positive for Aedes spp. Despite the region’s physiographic, climatic, and anthropogenic diversity, the districts shared a similar pattern of species distribution - A. albopictus was found in both rural and urban locations of all the districts while A. aegypti was observed in only urban locations of thirteen districts.  In some locations, both species were found to be co-existing in the same habitat containers. Mean larval density and mean container index were both higher in urban habitats than in rural areas though few rural locations showed significantly high density of larval population. The current findings of this survey thus provide a comprehensive picture of Aedes distribution in the said area and may in turn act as a foundation for more effective surveillance to characterize these vectors and to identify potential dengue outbreak hotspots in Southern West Bengal.